2005
DOI: 10.1293/tox.18.203
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Toxicity Study of Bisphenol A, Nonylphenol, and Genistein in Neonatally Exposed Rats

Abstract: Abstract:To investigate the endocrine-mediated effects of neonatal administration of the weak estrogenic compounds, bisphenol A, nonylphenol and genistein, were subcutaneously injected with these compounds at doses of 0.1, 1, and 10 µg/rat/day for 5 days starting on postnatal day 1. Rats were autopsied at 47-50 days. Positive control groups were given diethylstilbestrol (DES) at the same dose levels as the other chemicals. The ano-genital distance, age of vaginal opening and preputial separation, and estrus cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Estrogens including phytoestrogens such as genistein were found to impair gonadal development and spermatogenesis [10,14,17,19,20,24,26]. It is well known that licorice possesses estrogenic activity [22,35,36,39,40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estrogens including phytoestrogens such as genistein were found to impair gonadal development and spermatogenesis [10,14,17,19,20,24,26]. It is well known that licorice possesses estrogenic activity [22,35,36,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Females and mice are more vulnerable than males and rats. It is known that licorice contains phytoestrogens such as glabridin, hispaglabridins, glabrene, isoliquiritigenin and isoprenyl as well as genistein [26,35,39,40]. It is of interest to note that low levels of phytoestrogens in rodent chow enhance epididymal sperm counts via a-estrogen receptors [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noda et al (2005), support not indicated, examined the effect of neonatal bisphenol A exposure on reproductive organs of Sprague-Dawley rats. For 5 days beginning on PND 1 (day of birth 5 PND 0), 6-10 pups/sex/group (drawn from 2 litters) were s.c. injected with olive oil vehicle or bisphenol A [purity not reported] at 0.0001, 0.001, or 0.010 mg/rat/day.…”
Section: Utility (Adequacy) For Cerhr Evaluation Processmentioning
confidence: 99%
“…A study has shown that chronic application of NP can impair learning and memory and decrease exploratory activity in male mice (Mao et al, 2010). In contrast, some pre-viously performed studies did not show any effect on the reproductive tract after neonatal exposure to NP (Odum and Ashby, 2000;Noda et al, 2006). Additionally, perinatal exposure to NP did not affect locomotor activity or learning and memory performance in rat offspring (Flynn et al, 2002;Ferguson et al, 2000;Negishi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%